2012
DOI: 10.1021/es301129h
|View full text |Cite
|
Sign up to set email alerts
|

Subchronic Inhalation Exposure Study of an Airborne Polychlorinated Biphenyl Mixture Resembling the Chicago Ambient Air Congener Profile

Abstract: Although inhalation of atmospheric PCBs is the most universal exposure route and has become a substantial concern in urban areas, research is lacking to determine the body burden of inhaled PCBs and consequent health effects. To reflect the Chicago airshed environment and mimic the PCB profile in Chicago air, we generated vapors from a Chicago Air Mixture (CAM). Sprague-Dawley rats were exposed to the CAM vapor for 1.6 hr/day via nose-only inhalation for 4 wks, 520±10 μg/m3. Congener-specific quantification in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
1
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 34 publications
1
45
1
2
Order By: Relevance
“…Pure CB11 vapor was generated into our exposure system as previously described for PCB mixtures (23). Briefly, clean dry air (4.0 L/min) was bubbled through neat CB11 in an impinger held at 25.0°C in a precision water bath (Thermo Scientific, Portsmouth, NH).…”
Section: Methodsmentioning
confidence: 99%
“…Pure CB11 vapor was generated into our exposure system as previously described for PCB mixtures (23). Briefly, clean dry air (4.0 L/min) was bubbled through neat CB11 in an impinger held at 25.0°C in a precision water bath (Thermo Scientific, Portsmouth, NH).…”
Section: Methodsmentioning
confidence: 99%
“…Initial laboratory studies with animals and plants have demonstrated the potential of PCB 11 to become bioavailable to humans through inhalation and to be accessible for biotransformation (Hu et al, 2013, Zhu et al, 2013, Hu et al, 2012, Hu et al, 2010b, Hu et al, 2014). In 2013, PCB 11 was reportedly detected in human serum for the first time, thereby further emphasizing the need for a better understanding of the exposure, metabolism and toxicities of nonlegacy PCBs (Marek et al, 2013b).…”
Section: Environmental Sources Of Pcbsmentioning
confidence: 99%
“…The observation that certain C-PCBs have considerable concentrations in indoor air from US schools represents a particular public health concern (Thomas et al 2012). Recent nose-only inhalation studies demonstrate the PCBs, including some C-PCBs, are absorbed in the lung and distributed systemically in rats (Hu et al 2010, Hu et al 2012b). The uptake of PCBs in the lung appears to be highly efficient, with a 99.8% pulmonary uptake of an inhaled, radiolabeled PCB reported in rats (Hu et al 2014).…”
Section: Absorption Of C-pcbsmentioning
confidence: 99%